Effects of three patterns of elevated CO2 in single and multiple generations on photosynthesis and stomatal features in rice. (27th January 2023) - Yang, Kai; Huang, Yao; Yang, Jingrui; Lv, Chunhua; Hu, Zhenghua; Yu, Lingfei; Sun, Wenjuan
Abstract: Background and Aims: Effects of elevated CO2 ( E ) within a generation on photosynthesis and stomatal features have been well documented in crops; however, long-term responses to gradually elevated CO2 ( E g ) and abruptly elevated CO2 ( E a ) over multiple generations remain scarce. Methods: Japonica rice plants grown in open-top chambers were tested in the first generation (F1) under E a and in the fifth generation (F5) under E g and E a, as follows: E a in F1: ambient CO2 ( A ) + 200 μmol mol −1 ; E g in F5: an increase of A + 40 μmol mol −1 year −1 until A + 200 μmol mol −1 from 2016 to 2020; E a in F5: A + 200 μmol mol −1 from 2016 to 2020. For multigenerational tests, the harvested seeds were grown continuously in the following year in the respective CO2 environments. Key Results: The responses to E a in F1 were consistent with the previous consensus, such as the occurrence of photosynthetic acclimation, stimulation of photosynthesis, and downregulation of photosynthetic physiological parameters and stomatal area. In contrast, multigenerational exposure to both E g and E a did not induce photosynthetic acclimation, but stimulated greater photosynthesis and had little effect on the photosynthetic physiology and stomatal traits. This suggests that E retained intergenerational effects on photosynthesis and stomatal features and that there were no multigenerational differences in the effects of E g and E a . Conclusions: The present study demonstrated that projecting future changes induced by E based on the physiological responses of contemporary plants could be misleading. Thus, responses of plants to large and rapid environmental changes within a generation cannot predict the long-term response of plants to natural environmental changes over multiple generations, especially in annual herbs with short life cycles.